Experiences of patients who had a stroke and rehabilitation professionals with upper limb rehabilitation robots: a qualitative systematic review protocol. Issue 9 (19th September 2022) - Chockalingam, Manigandan; Vasanthan, Lenny Thinagaran; Balasubramanian, Sivakumar; Sriram, Vimal
Abstract : Introduction: Emerging evidence suggests that robotic devices for upper limb rehabilitation after a stroke may improve upper limb function. For robotic upper limb rehabilitation in stroke to be successful, patients' experiences and those of the rehabilitation professionals must be considered. Therefore, this review aims to synthesise the available evidence on experiences of patients after a stroke with rehabilitation robots for upper limb rehabilitation and the experiences of rehabilitation professionals with rehabilitation robots for upper limb stroke rehabilitation. Methods and analysis: Database search will include MEDLINE (Ovid), EMBASE (Elsevier), Cochrane CENTRAL, PsycINFO, Scopus, Web of Science, IEEE and CINAHL (EBSCOhost). Grey literature from Open Grey, PsyArXiv, bioRxiv, medRxiv and Google Scholar will also be searched. Qualitative studies or results from mixed-method studies that include adult patients after a stroke who use upper limb rehabilitation robots, either supervised by rehabilitation professionals or by patients themselves, at any stage of their rehabilitation and/or stroke professionals who use upper limb rehabilitation robots will be included. Robotic upper limb rehabilitation provided by students, healthcare assistants, technicians, non-professional caregivers, family caregivers, volunteer caregivers or other informal caregivers will be excluded. Articles published in English will be considered regardless of date of publication. Studies will be screened and critically appraised for methodological quality by two independent reviewers. A standardised tool from JBI System for the Unified Management, Assessment and Review of Information for data extraction, the meta-aggregation approach for data synthesis and the ConQual approach for confidence evaluation will be followed. Ethics and dissemination: As this systematic review is based on previously published research, no informed consent or ethical approval is required. It is anticipated that this systematic review will highlight the experiences of patients after a stroke and perceived facilitators and barriers for rehabilitation professionals on this topic, which will be disseminated through peer-reviewed publications and national and international conferences. PROSPERO registration number: CRD42022321402.